2021
DOI: 10.25115/eea.v39i1.3448
|View full text |Cite
|
Sign up to set email alerts
|

Export, Political Stability, and Growth in Developing-8 Countries

Abstract: The relationship between growth in export and economic growth is still a current issue in both the theoretical and empirical literature. Besides, there are also non-economic factors that determine economic growth in a country, namely political stability. This study aims to examine the impact of export and political stability on economic growth in D8 member countries. The research on the development of the D8 country's economy is still minimal, so this research expected to be able to contribute to drafting poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This result also oposite with Edo et al (2020) that also found the insignificant impact of export on economic growth in the short-run. Al Arif et al (2021) also found that export doesn't have an impact on economic growth in D-8 countries.…”
Section: Resultsmentioning
confidence: 98%
“…This result also oposite with Edo et al (2020) that also found the insignificant impact of export on economic growth in the short-run. Al Arif et al (2021) also found that export doesn't have an impact on economic growth in D-8 countries.…”
Section: Resultsmentioning
confidence: 98%